Wide-Bandgap GaN Based Modular Multilevel Converter for High Power Motor Drives: Loss Modeling and Thermal Optimization - Sudirman, Ridwan (Journal of Electrical Engineering, 2024)
This research addresses the development of a Wide-Bandgap Gallium Nitride (GaN)-based Modular Multilevel Converter (MMC) for high-power motor drives, with a focus on loss modeling and thermal optimization. The use of GaN devices enables operation at high switching frequencies and high voltages, thereby improving system efficiency and reducing the size of passive components. However, operation at high power also poses challenges related to thermal management and loss distribution in the MMC modules. This research models conduction losses, switching losses, and losses in passive components, then integrates them into a thermal analysis to identify hotspots and optimize cooling. This approach involves simulating a GaN MMC under various high-power motor operating conditions to assess loss distribution and temperature profiles. Simulation results show that an integrated thermal design strategy can reduce the peak device temperature by 15–20% compared to conventional designs, while maintaining high energy conversion efficiency (>98%). This thermal optimization also allows the use of higher switching frequencies, which contributes to the reduction of inductor and capacitor sizes in the system. This research makes an important contribution to the design of GaN-based modular converters for high-power motor applications, with a combination of high efficiency, effective heat management, and system size optimization.